Insulin-Like Growth Factor-1, a Potential Predicative Biomarker for Postoperative Delirium Among Elderly Patients with Open Abdominal Surgery - Shen, Huachun; Shao, Yi; Chen, Junping; Guo, Jianrong (Current Pharmaceutical Design, 2016)
Background: Delirium is commonly observed among elderly surgical subjects during the postoperative period, and the incidence of postoperative delirium (POD) in elderly patients (≥65 years) ranges widely from 10% to 70%. This study aimed at investigating potential serum predicative factors for POD in elderly patients after open abdominal surgery. Methods: 140 subjects scheduled to undergo elective gastrointestinal tumor resection via laparotomy from March, 2013 to May, 2015 were enrolled in this study. Participants enrolled were evaluated for delirium and delirium severity on preoperative day, postoperative days 2 and 3. Non-fasting blood samples were collected in the morning on the day before surgery for the detection of serum cytokines expressions by enzyme-linked immunesorbent assays (ELISA). Results: A total of 140 patients were finally enrolled in this study and 36 of them occurred POD, with a POD incidence of 25.7%. In comparison with non-POD group, the serum levels of insulin-like growth factor-1 (IGF-1) demonstrated significantly decreased of patients in POD group (P<0.01). The receiver operating characteristic (ROC) curve analysis revealed that serum IGF-1 levels as potential predicative factor for POD with the area under the ROC curve (AUC) values of 0. 805, with 95 % confidence interval (CI) of 0.719-0.891 (P<0.001). Univariate and multivariate logistic regression analysis resulted in serum IGF-1 level as a non-invasive predicative factor for POD (OR=2.52, 95%CI: 1.19-5.43, P=0.019). Conclusion: Our results showed that serum IGF-1 level was a potential predicative biomarker for POD among patients undergoing elective gastrointestinal tumor resection via laparotomy.
Keywords: Postoperative delirium